모래하천에서 식생 침입에 대한 육상곤충 군집의 반응 - 조건호(Geonho Cho); 조강현(Kang-Hyun Cho) (Ecology and Resilient Infrastructure, 2017)
In order to investigate the response in fauna and biological communities of terrestrial insects to the vegetation encroachment on the sandbar, species composition, species diversity, functional species traits and community structure of land-dwelling insects sampled by a pit-fall trap were compared at the bare and vegetated sandbar of a typical sand-bed stream, the Naeseong Stream, Korea. Species diversity of the insects was increased but their density was decreased as the riparian vegetation encroached at the sandbar. In particular, indicator species of bare sandbar such as Cicindela laetescripta and Dianemobius csikii, were found at the bar sandbar. The insect communities were clearly classified at the bare and vegetated sandbar according to coverages of riparian plants. The food web of the bare sandbar was composed of detritus - detritivore and scavenger - predator consisted mainly of Coleoptera. On the other hand, the food web of the vegetated sandbar was composed of plants - sucking and chewing herbivore - parasitoid and predator. These results showed that biodiversity of terrestrial insects was increased, food web was changed from grazing to detritus food chain, and insect fauna specific bare sandbar disappeared as the riparian vegetation invaded on the sandbar of a sand-bed stream. 대표적 모래하천인 내성천의 사주에서 식생 정착에 대한 지면 서식 육상곤충의 생물상과 생물군집의 반응을 파악하기 위하여, 나지 사주와 식생 사주에서 함정법으로 곤충을 채집하여 종조성, 종다양성, 기능특성군 및 생물군집 구조를 비교하였다. 내성천에서 육상곤충은 나지사주에 식생이 정착함에 따라서 서식 곤충의 종다양성은 증가하였으나 서식 밀도는 감소하였다. 특히 나지 사주에서는 강변길앞잡이, 동양알락방울벌레 등의 사주 지표성 곤충이 서식하였다. 사주의 곤충군집은 사주 식생의 피도에 따라서 나지사주와 식생사주로 뚜렷하게 구분되었다. 모래하천의 나지 사주의 먹이망은 쇄설물 - 쇄설물 섭식자와 청소자 - 주로 딱정벌레목에 속하는 포식자로 구성되었다. 반면에 식생 사주 먹이망은 식물 - 흡즙 초식자와 저작 초식자 - 포식기생자와 포식자로 구성되었다. 결론적으로 모래하천에서 나지 사주에 식생에 정착함에 따라서 종다양성은 증가하고 초식 먹이사슬로 변화하고, 나지 사주에 특이적인 곤충상과 쇄설물 기반 먹이사슬이 사라지는 것으로 판단되었다.